Child Maintenance under the Divorce Act - Payne, Julien; Shipton-Mitchell, Cindy (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1984)
As courts increasingly endorse policies of a clean financial break between divorcing spouses and rehabilitative spousal support orders on the breakdown of marriage, the importance of the law respecting child maintenance on the dissolution of marriage is correspondingly increased. This article seeks to define the law in this context, without obfuscating those issues that remain controversial before the courts. The analysis defines which children are protected by the corollary financial provisions of the Divorce Act, R.C.S., 1980, c. D-8; the circumstances in which an application may be made; the potential duration of orders; the effect of spousal agreements; the respective degrees to which each spouse will be required to contribute towards the costs of rearing the child; the types of orders that can be made including retrospective orders; and the agreement, variation and rescission of child maintenance orders.